Spousal violence against women in Afghanistan: Bivariate mapping of correlates - Masood Ali Shaikh (Journal of the Pakistan Medical Association, 2022)
genesis to deeply entrenched socio-cultural norms. In this study 2015 Demographic and Health Survey data for Afghanistan was used to calculate the provincial prevalence and two correlates of spousal violence, and their bivariate mapping. Large differences were present in the provincial prevalence of spousal violence, having witnessed their father ever beat their mother, and acceptance of spousal violence by the currently or ever married women aged 15-49 years. In general, bivariate maps showed strong associations between spousal violence against women, its acceptance by women, and having witnessed their father beat their mother by ever married women. In an easily comprehensible manner, these maps underscore ensuring better quality of life in marital settings, higher and more equal social stature of women, and protecting their basic human rights would entail legal, social, and cultural paradigm shift. Keywords: Domestic Violence, Intimate Partner Violence, Afghanistan, Women, Abuse.